Implementing Joyful Learning Strategies to Foster Student Learning Interest and Discipline in Elementary Education - Sonya Pramaswarii Hadi; Ahmad Fauzan; Yudesta Erfayliana (Universitas Negeri Medan, 2026)
This study aims to describe the implementation of the Joyful Learning strategy in improving students’ learning interest and discipline at SD Al-Azhar 1 Bandar Lampung. This study employed a qualitative approach with a descriptive research design, involving 2 teachers (the vice-principal of curriculum and a homeroom teacher) and 27 students as research subjects. Data were gathered through observations, interviews, and documentation, then analyzed using thematic reduction. The results showed that joyful learning—implemented through structured educational games and interactive media—effectively bridged emotional engagement and behavioral regulation. Descriptive data revealed that the 27 students demonstrated a significant increase in situational interest during gamified sessions, despite varying levels of enthusiasm. Crucially, the qualitative mechanism showed that the